Economic integration among ASEAN countries: evidence from gravity model - Mohd Amin, Ruzita; Hamid, Zarinah; Md Saad, Norma (East Asian Development Network, 2009)
This study aims at investigating whether intra-ASEAN trade is trade creating (higher trade with efficient members) or trade diverting (higher trade with inefficient members) for both inter-industry and intra-industry trade. Since integration efforts within ASEAN had to be geared toward “open regionalism”, factors that affect trade, both inter-industry as well as intra-industry trade at the sectoral level are also identified. The study adopts the extended gravity model at the total as well as the disaggregated level using the one-digit Standard International Trade Classification (SITC) Revision 2. Trade creation is found to be present for total exports, for beverages & tobacco (SITC 1), chemicals & materials (SITC 5),machinery & transport equipment (SITC 7),and miscellaneous manufactures (SITC 8). Income levels, transportation costs as well as level of development have significant effects on total trade as well as most sectors. Relative development affects only food & live animals (SITC 0), crude materials (SITC 2), chemicals & materials (SITC 5), and manufactured goods (SITC 6). Factor endowments are important determinants of total trade as well as trade in animal & vegetable fat (SITC 4), chemicals & materials SITC 5), machinery & transport equipment (SITC7), and miscellaneous manufactures (SITC 8).Tariffs do not seem to have any effect on trade except for the animal & vegetable fat sector (SITC 4), while exchange rate risk affects only beverages & tobacco (SITC 1), minerals & fuels (SITC 3), machinery & transport equipment (SITC 7), and miscellaneous manufactures (SITC 8). Based on the findings, in general, policies that promote growth and development in the region should be maintained. In addition, measures need to be undertaken to ensure low transportation costs that include improving both the physical infrastructure and the efficiency of transportation systems. Since tariffs are no longer much of an issue to promote trade, emphasis should be placed on other factors that may affect export demand such as product development to improve the quality of exports and to meet the preferences of importing countries.